2005
DOI: 10.1245/aso.2005.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Extracapsular Extension of Axillary Lymph Node Metastases in T1 to T3 Breast Cancer

Abstract: ECE demonstrated a stronger statistical significance in predicting prognosis than the pN category and was also related to an increased risk of distant recurrences. We suggest that the decision on adjuvant therapy should consider the presence of ECE of axillary metastases and peritumoral LVI as indicators of high biological aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 21 publications
2
21
1
Order By: Relevance
“…In another report LVI was associated with the presence of more than 4 axillary nodes, and primary tumor size was strongly associated with regional recurrence (29). In addition, LVI and ECE showed statistically significant differences for disease-free survival (30).…”
Section: Discussionmentioning
confidence: 90%
“…In another report LVI was associated with the presence of more than 4 axillary nodes, and primary tumor size was strongly associated with regional recurrence (29). In addition, LVI and ECE showed statistically significant differences for disease-free survival (30).…”
Section: Discussionmentioning
confidence: 90%
“…The presence of ENI increases the possibility of locoregional and systemic metastases while decreasing disease-free survival and overall survival rates as has been stated in some studies [7,[12][13][14][15]. Because of this, in ENI positive cases postmastectomy radiotheraphy and more effective chemotheraphy protocols are offered to prevent locoregional recurrences [6].…”
Section: Discussionmentioning
confidence: 97%
“…According to our results, LVI can also be accepted as a predictor of an aggressive tumour, in that the presence of LVI has increased up to 73% when the nuclear grade has been determined as 3, whereas there is no positive LVI in nuclear grade 1 tumours in our patients. NERI et al (9) have also reported that the decision to apply adjuvant therapy should consider the presence of LVI as an indicator of high biological aggressiveness.…”
Section: Discussionmentioning
confidence: 99%